Circle of days : a novel - Follett, Ken (Grand Central Publishing, 2025)
"Seft, a talented flint miner, walks the Great Plain in the high summer heat, to witness the rituals that signal the start of a new year. He is there to trade his stone at the Midsummer Rite, and to find Neen, the girl he loves. Her family live in prosperity and offer Seft an escape from his brutish father and brothers, within their herder community. Joia, Neen's sister, is a priestess with a vision and an unmatched ability to lead. As a child, she watches the Midsummer ceremony, enthralled, and dreams of a miraculous new monument, raised from the biggest stones in the world. But trouble is brewing among the hills and woodlands of the Great Plain. Joia's vision of a great stone circle, assembled by the divided tribes of the Plain, will inspire Seft and become their life's work. But as drought ravages the earth, mistrust grows between the herders, farmers and woodlanders - and an act of savage violence leads to open warfare.."-- Provided by publisher.